Treatment of rheumatoid arthritis (RA) in India—how and by whom: results from a speciality clinic—use of low-dose methotrexate (MTX) was inexplicably suboptimal. Issue 9 (September 2016) - Malaviya, Anand; Gogia, S.
Abstract This study was conducted in order to study (a) seropositive RA patients for their prior caregivers, diagnosis makers, drugs and doses taken and (b) the disease status at the first visit and the last visit, from the standpoint of whether they received optimum or suboptimum DMARD treatment. Prospectively entered data were extracted from a rheumatology-specific electronic health record for demography, diagnostic delay, prior caregivers, diagnosis makers, intake of DMARDs and glucocorticoids and disease activity state at first presentation and at the last visit using structured query language. Among 316 patients, prior caregivers were orthopaedicians (73.4 %), alternative systems of medicine practitioners (62 %), internists (38 %), rheumatologists (35.8 %), general practitioners (17 %) and others (12 %). The diagnosis of RA was made by rheumatologists (55.6 %), orthopaedicians (21 %), internists (12.6 %), physiotherapists (3.5 %), homeopaths (2.8 %), general practitioner (2.1 %), neurologists (1.4 %) and Ayurvedic physicians (0.7 %). The mean and the median diagnostic delay among 142 patients where information was available were 18 and 8.5 months, respectively (SD+ 23.2). Thirty-two percent of the patients had early disease, 48 % established disease and 20 % late disease at presentation. Sixty-six percent of the patients had taken DMARDs—methotrexate (56 %), hydroxychloroquine (46.2 %), leflunomide (18.7 %) and sulfasalazine (20.6 %)—and often in combinations. Different preparations, doses and schedules of glucocorticoids were taken orally or parentally by 51 %. Only one (0.3 %) patient had taken biological DMARDs prior to visiting this clinic. High or moderate disease activity was present in 84 % at the first clinic visit that fell to 14 % at the last clinic visit. The majority of patients with RA were treated by orthopaedicians and practitioners of alternative systems of medicine with only a third by rheumatologists. In 80 % of patients, the diagnosis was made 18 months at the onset, yet in 84 %, the disease control was poor. Non-use or suboptimal use of methotrexate appeared to be the main reason.